2016
DOI: 10.14686/buefad.v5i3.5000193186
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Çocuklarının Bilim İnsanı Kavramına Yönelik Algıları

Abstract: Özet: Bu çalışma okul öncesi dönemde bulunan çocukların bilim insanı kavramına yönelik algılarını belirlemek amacıyla yapılmıştır. Araştırmanın katılımcılarını Trabzon ili Beşikdüzü ilçesinden rastgele seçilen iki anaokulunda öğrenim gören 48-72 ay aralığındaki 68 çocuk oluşturmaktadır. Veriler, Chambers'in (1983) "Bir Bilim İnsanı Çiz Testi" ve derinlemesine mülakat tekniği ile toplanmıştır. Elde edilen veriler, araştırma üçgenlemesi yöntemi ile uzman görüşüne başvurularak temalar oluşturulmuş ve bu temalara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
(11 reference statements)
3
8
0
2
Order By: Relevance
“…Almost half of the girls drew the scientist as female and more than half of them drew as a man. Ayvacı et al (2016) found similar results in 48-72 monthold children's perceptions of scientist. Gonsoulin (2001) obtained similar results and stated that interestingly, male students drew a male scientist and female students drew only female scientist.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Almost half of the girls drew the scientist as female and more than half of them drew as a man. Ayvacı et al (2016) found similar results in 48-72 monthold children's perceptions of scientist. Gonsoulin (2001) obtained similar results and stated that interestingly, male students drew a male scientist and female students drew only female scientist.…”
Section: Discussionsupporting
confidence: 65%
“…It was determined in the study conducted with 4800 children in the United Stateds, Australia, and Canada by Chambers (1983) that scientists were generally perceived as being male, bearded, having messy hair, glasses, wearing lab coats, and being engaged in test materials. Similar studies have been conducted by many researchers with children of different age groups (Ayvacı, Atik and Ürey, 2016;Finson, Beaver and Cramond, 1995;Flick, 1990;Güler and Akman, 2006;Huber and Burton, 1995;Kara and Akarsu, 2013;Kaya, Doğan and Öcal, 2008;Koballa, 1998;Koren and Bar, 2009;Krajkovich and Smith, 1982;Mason, Kahle and Gardner, 1991;Özgelen, 2012;Özsoy and Ahi, 2014;Rosenthal, 1993;Schibeci and Sorensen, 1983;Toğrol-Yontar, 2000;Türkmen, 2008). In the findings obtained from the studies, it was observed that children's stereotypical perceptions of scientists were male, working indoor area, wearing glasses, with test tubes, books, scattered hair and beard.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Özellikle son yıllarda, çocukların araştırmaya dâhil edilmesine ve onların algı, düşünce ve duygularının kendilerinden elde edilmesine büyük önem verilmektedir (Christensen ve James, 2000). Bu çalışmaların yapımı sırasında sadece sözel araçların değil, görsel ve sanatsal ürünlerin de metaforik algıları destekleme noktasında kullanıldığı görülmektedir (Kindap ve Sayil, 2005;Ahi, Cingi ve Kıldan, 2016;Ayvacı, Atik ve Ürey, 2016;Sezgin ve Hatipoğlu, 2017;Şener, 2018;Civek ve Çakmak, 2019;Bay, Geyik ve Çalışkan, 2019). Bu nedenle çizimler ve beraberindeki anlatımlar birbirlerinden ayrı iki süreç olarak düşünülmemelidir.…”
Section: Introductionunclassified